Education on the Use of Herbal Plants in the Community to Increase Knowledge in the Use and Manufacture of Herbal Plants - Aryzki, Saftia; Okvianingsih, Arum Dwi; Humaira, Muhammad Nurridho Alfian; Astuti, Puspita; Norliani, Rahma; Rahmawati, Siti (Universitas Lambung Mangkurat, 2025)
Education about the use of herbal plants is a step taken to increase public knowledge and empower the potential of medicinal plants. Education aims to increase knowledge in the use and preparation of herbal plants. Some of which people often use are ginger, lemongrass, cinnamon and turmeric. Respondents in the service were from the community in the RT. 16 North Alalak Subdistrict. The ABCD method focuses on the potential assets to be observed, namely herbal plants which are easily obtained by the people of Alalak Utara Subdistrict RT 16 by conducting surveys and distributing leaflets. The data collection technique uses a questionnaire. Based on the results obtained, before the educational activities were carried out and after the educational activities were carried out, the value was obtained from 35% to 100%. Thus, it can be concluded that in this educational activity, there was an increase in knowledge of the use of herbal plants by 65%.